Rings and Mules in Britain: Reply - Lazonick, William (Quarterly Journal of Economics, 1984)
Journal Article Rings and Mules in Britain: Reply Get access William Lazonick William Lazonick Harvard University Search for other works by this author on: Oxford Academic Google Scholar The Quarterly Journal of Economics, Volume 99, Issue 2, May 1984, Pages 393–398, https://doi.org/10.2307/1885535 Published: 01 May 1984